Strategies For Developing Organizational Culture at SMKN 3 Mandau and SMKN Integrated Agriculture Pekanbaru, Riau Province - Tutut Handayani; Meilina Bustari (Journal of Educational Sciences, 2026)
The transformation of vocational schools into SMK Pusat Keunggulan (SMK PK) requires strong organizational culture as a foundation for sustainable improvement. This study aims to analyze the forms of organizational culture, the process of its development, the obstacles encountered, and the strategies used to overcome barriers in SMKN 3 Mandau and SMKN Pertanian Terpadu Pekanbaru. A qualitative case study approach was employed. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using the Interactive Model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings show that both schools develop organizational culture based on discipline, cleanliness, cooperation, religiosity, and industrial work culture. Cultural development is conducted through inclusive planning, integration into routine activities, collaboration with industry partners, and continuous supervision. Major obstacles include declining student work ethics, limited industrial partner involvement, and differing levels of cultural internalization among teachers and students. The schools address these challenges by strengthening discipline routines, expanding industry partnerships, and enhancing communication with parents and stakeholders. The study concludes that systematic and collaborative organizational culture development significantly supports the effectiveness of SMK PK implementation.